Equilibrium properties of the lattice system with SALR interaction potential on a square lattice: quasi-chemical approximation versus Monte Carlo simulation - Groda, Ya.G.; Vikhrenko, V.S.; D. di Caprio (Condensed Matter Physics, 2018)
The lattice system with competing interactions that models biological objects (colloids, ensembles of protein
molecules, etc.) is considered. This system is the lattice fluid on a square lattice with attractive interaction
between nearest neighbours and repulsive interaction between next-next-nearest neighbours. The geometric
order parameter is introduced for describing the ordered phases in this system. The critical value of the order parameter is estimated and the phase diagram of the system is constructed. The simple quasi-chemical
approximation (QChA) is proposed for the system under consideration. The data of Monte Carlo simulation of
equilibrium properties of the model are compared with the results of QChA. It is shown that QChA provides
reasonable semiquantitative results for the systems studied and can be used as the basis for next order approximations. Розглядається ґраткова система з конкурентними взаємодiями, що моделює бiологiчнi об’єкти (колоїди,
ансамблi протеїнових молекул i т.д.). Ця система представляється ґратковим плином на квадратнiй ґратцi
з притягальною взаємодiєю мiж найближчими сусiдами i вiдштовхувальною взаємодiєю мiж наступними
за наступними до найближчих сусiдiв. Для опису впорядкованої фази в такiй системi вводиться геометричний параметр порядку. Зроблена оцiнка критичного значення параметра порядку i побудована фазова дiаграма системи. Для системи, що розглядається, запропоновано просте квазiхiмiчне наближення
(КХН). Данi симуляцiй Монте Карло рiвноважних властивостей моделi порiвнюються з результатами КХН.
Показано, що КХН забезпечує прийнятнi напiвкiлькiснi результати для системи, що вивчається, i може
використовуватися як базис для наступних наближень.